2018
DOI: 10.1109/tit.2018.2818736
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Regions of Two-Receiver Broadcast Erasure Channels With Feedback and Memory

Abstract: The two-receiver broadcast packet erasure channel with feedback and memory is studied. Memory is modeled using a finitestate Markov chain representing a channel state. Two scenarios are considered: (i) when the transmitter has causal knowledge of the channel state (i.e., the state is visible), and (ii) when the channel state is unknown at the transmitter, but observations of it are available at the transmitter through feedback (i.e., the state is hidden). In both scenarios, matching outer and inner bounds on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Previously, there have been two primary techniques in deriving a rate region for queue-based coding schemes, which we have found to be insufficient for our purposes. The first technique was derived from a channel coding problem involving erasure channels with feedback and memory [5]. In [5], the authors use a queue stability criterion to set up a system of inequalities involving the achievable rates and flow variables that represent the number of packets that are transferred between queues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, there have been two primary techniques in deriving a rate region for queue-based coding schemes, which we have found to be insufficient for our purposes. The first technique was derived from a channel coding problem involving erasure channels with feedback and memory [5]. In [5], the authors use a queue stability criterion to set up a system of inequalities involving the achievable rates and flow variables that represent the number of packets that are transferred between queues.…”
Section: Introductionmentioning
confidence: 99%
“…The first technique was derived from a channel coding problem involving erasure channels with feedback and memory [5]. In [5], the authors use a queue stability criterion to set up a system of inequalities involving the achievable rates and flow variables that represent the number of packets that are transferred between queues. When this technique is applied to the chaining algorithm of Section III-B2 however, we find that our system of inequalities is over-specified.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we aim to shed light on the interplay between AoI and (channel/network) coding in the context of broadcast packet erasure channels (BPECs) with feedback. BPECs and their variants have been investigated in previous work such as [35]- [39] and rate-optimal coding algorithms are designed using (network) coding ideas. The key idea is due to [35] where it is shown that the entire capacity region of two-user BPECs with feedback can be attained by XORing overheard packets.…”
Section: Introductionmentioning
confidence: 99%
“…Although the theoretical result is well beyond the V2I scenario, we do believe that this scenario is one of the few cases for which the underlying assumptions of the general result can be realistic. In contrast to previous works on similar setups [9], [10] which use queuing-theoretic tools, we adopt an Information-Theoretic (IT) approach to derive the achievable rate region. Our scheme is based on standard IT tools such as random coding arguments, block Markov coding, joint source-channel coding and typicality decoding.…”
Section: Introductionmentioning
confidence: 99%